2017
DOI: 10.1021/acs.energyfuels.6b02874
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Lean Extinction of Premixed Flames Stabilized on Conductive Perforated Plates

Abstract: The structure and lean extinction of premixed liquefied petroleum gas–air flames seated on conductive perforated plates were examined experimentally, with focus on the effects of plate material, thickness, and hole diameter. The lean extinction limit was determined by gradually reducing the fuel-flow rate for a given air-flow rate, until extinction occurred. Flame structure was quantified by mapping the local mean temperature and species concentrations and by imaging the average visual length of the flame plum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The data contain 21,600 samples of Steam Flow Rate (SFR) with sampling rate of 1 s. The behavior of all the other variables is simulated using Å stro¨m and Bell's model 7 of boiler. The results of that are validated against experimental data and extensively discussed in Elshafei et al 12 and Gamal et al; 29 but using our PID gains, the entire system is simulated again to provide a modest overview of available results in the literatures. Also, dynamic optimization of efficiency with NOx is examined and detailed discussion is presented in section ''Optimization, results and discussion'' along with simulation results.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…The data contain 21,600 samples of Steam Flow Rate (SFR) with sampling rate of 1 s. The behavior of all the other variables is simulated using Å stro¨m and Bell's model 7 of boiler. The results of that are validated against experimental data and extensively discussed in Elshafei et al 12 and Gamal et al; 29 but using our PID gains, the entire system is simulated again to provide a modest overview of available results in the literatures. Also, dynamic optimization of efficiency with NOx is examined and detailed discussion is presented in section ''Optimization, results and discussion'' along with simulation results.…”
Section: Introductionmentioning
confidence: 58%
“…Mixing of fuel and air upstream of the combustion in case of premixed flames can reduce the combustion temperature at the same FFR when compared to diffusion flames. 29 This means that the combustion temperature can be controlled at fixed FFR. Using this conversion factor, the upper limit of NOx is calculated to be 100 ppm It is also noteworthy that this value is dependent on AFR which varies under dynamic conditions and so does the upper limit of NOx in ppm.…”
Section: Nox Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conductive plates were considered with thermal conductivities up to 10 W/m·K only. Jamal et al, 231 however, considered conductivity values as high as 385 W/m·K and proved that if considerable heat is transferred through the plate to preheat the incoming combustible mixture, the flames become shorter and more stable. The authors examined the effects of plate material, thickness, and hole diameter and showed that heat transfer through the plate is the hidden primary control parameter behind all these effects.…”
Section: Pp Burnersmentioning
confidence: 99%
“…The swirl is implemented in the air side or the annulus side of the combustor. The swirl number Sn is defined as the ratio of the tangential momentum flux over the axial momentum flux, and it is calculated from the following equation: Chemical reactions under the stoichiometric conditions for the air-fuel and oxy-fuel combustion are presented in eqs and , respectively, , where α is the oxygen fraction. It can be defined as the mole fraction of oxygen in the oxidizer blends can be identified by the following formula of eq where V O 2 ° and V O 2 ° denoted the volumetric flow rate of and carbon dioxide in the oxidizer mixture.…”
Section: Modeling Of the Combustormentioning
confidence: 99%